Atributos químicos e matéria orgânica do solo sob diferentes manejos em Latossolo do Cerrado - Facco, Daniela Basso (2020)
Cotton (Gossypium hirsutum L.) is an important agricultural crop in the Brazilian Cerrado region and is frequently grown under conventional soil tillage (CT), monoculture and/or in succession with grain crops, such as soybean (Glycine max L. Merrill). Therefore, the soils in areas under CT can have low quality and be in a process of degradation. Crop systems that involve no-tillage (NT) and cover crops in succession and/or rotation with the main crops are important and viable alternatives to the Cerrado’s production systems. These management practices promote changes in the soil chemical attributes, the soil organic matter (SOM) dynamics, and the overall soil quality. However, the intensity of such processes is yet not well understood for the Cerrado’s environment neither it’s reflexes on the grain crops productivity. Therefore, this study aims to evaluate the effect of different long-term management practices on the vertical nutrient distribution, SOM dynamics, soil quality and its influence on soybean yield in a heavy clay Oxisol. Stratified soil samples were collected in an experiment conducted by the Fundação MT in Itiquira - MT involving different crop systems [fallow, cotton, corn (Zea mays), soybean, millet (Pennisetum glaucum), brachiaria (Urochloa ruziziensis) and crotalaria (Crotalaria sp.)] and soil tillage (CT and NT) after 11 years of experiment conduction. Selected soil chemical properties (acidity attributes and nutrient availability indexes), total organic carbon (TOC), physical fractions of carbon, indexes of soil quality, and its relationship with soybean yield were analyzed. The NT presented better soil acidity conditions and nutrient availability in the soil superficial layer while presenting certain limitations below the soil top 10 cm layer. Moreover, the NT system has a strong gradient of nutrient availability along the soil profile, while at the CT the nutrients’ distribution was more homogeneous at the soil top 20 cm layer. The impact of both crop and soil tillage system on soil TOC and its fractions was more evident in the topsoil, where the highest TOC concentrations were observed under NT and in the cropping systems with cover crops. The most diversified cropping systems had little or no influence on the soil quality indexes [Carbon stock, Carbon Stratification Ratio (CSR), and Carbon Management Index (CMI)] but differed from the fallow system. Hence, the NT associated with diversified cropping systems has a greater capacity to enhance soil quality, which is evidenced by the higher CSR and CMI indexes values. Soybean yield was not affected by soil tillage but responded positively to the cropping systems, with lower yields occurring in the fallow system compared to the other cropping systems. The fallow crop system presented similar soil fertility levels but significantly lower yield than other cropping systems, which indicates that the soil quality was responsible for determining soybean productivity.